2013
DOI: 10.1371/journal.pone.0065356
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Major Depressive Disorder in Mainland China: A Systematic Review

Abstract: BackgroundMajor depressive disorder (MDD) is one of the important causes of disease burden in the general population. Given the experiencing rapid economic and social changes since the early 1990s and the internationally recognized diagnostic criteria and interview instruments across the surveys during 2001–2010 in china, the epidemiological studies on MDD got varied results. We performed this meta-analysis to investigate current, 12-month and lifetime prevalence rates of MDD in mainland China.MethodsPubMed, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
97
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(116 citation statements)
references
References 39 publications
16
97
2
1
Order By: Relevance
“…1 The disorder is the third leading cause of global disease burden, with annual total costs to society exceeding $80 billion worldwide, 2 and is predicted to be the leading health burden worldwide by 2030. 3 Numerous studies have reported cognitive dysregulation and behavioural and physical dysfunction in individuals with MDD.…”
Section: Introductionmentioning
confidence: 99%
“…1 The disorder is the third leading cause of global disease burden, with annual total costs to society exceeding $80 billion worldwide, 2 and is predicted to be the leading health burden worldwide by 2030. 3 Numerous studies have reported cognitive dysregulation and behavioural and physical dysfunction in individuals with MDD.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, patients with MDD are treated with antidepressant drugs, mainly including selective serotonin reuptake inhibitors (SSRIs) and serotonin-norepinephrine reuptake inhibitors (SNRIs); however, significant individual variability in antidepressant response has been observed in MDD patients (Cusin et al, 2002;Ferrari et al, 2013). It has been postulated that both genetic and environmental factors may have an impact on the variability of responses to antidepressant (Gu et al, 2013;Harkness et al, 2012). Many environmental factors have been identified to be associated with treatment response in MDD, such as childhood maltreatment, life stress and gender (Hong et al, 2006;Illi et al, 2009;Jankovic, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Using meta-analysis, Gu and colleagues revealed that the overall estimation of current, 12-month, and lifetime prevalence rates of MDD is 1.6%, 2.3%, and 3.3%, respectively; the current prevalence is 2.0% in rural areas and 1.7% in urban areas; and female prevalence is 2.1% and the male prevalence 1.3% [7]. An epidemiological study also reported that the weighted prevalence estimates for MDD in a southwestern city (Kunming) in China were 1.96% (lifetime), 1.09% (1 year), and 0.93% (1 month) [8].…”
Section: Epidemiology Of Mdd In Chinamentioning
confidence: 99%